Logical social similarities and imitation (Phenomenon influencing human thinking) - Yusifova, Gulnare Yusifqizi; Kazimi, Parviz Firudinoqlu (Edelweiss Applied Science and Technology, 2025)
The problem of logical social similarity and imitation has been studied very little by the humanities. Logical social similarities and imitation are important areas of thought and socio-cultural development. By separating the social aspects of man from the biological and physical, one can find that there are an extraordinary number of analogies between them. This area, which is of greatest interest to logic, psychoanalysis, and social psychology, once again confirms the need for a more in-depth study of analogy—one of the forms of inference studied at the rational level of cognition. The fact that imitated social phenomena have deep and very natural analogies with physical and biological phenomena necessitates their broader study. The research work "Logical Social Similarities and Imitation" is one of the most important problems in philosophy, logic, and fiction. At the beginning of the scientific research, the relevance of the topic was analyzed, as well as the works and views of philosophers on this problem in the history of philosophy. Furthermore, logical similarities and imitation, laws of imitation, logical duels, non-logical effects, imitation from internal to external, language, legislation, customs, requirements, etc., related to imitation are considered in detail. It is noted that as a continuation of scientific research, it is necessary to study the logical laws of imitation more fully and independently.